Remotely accessible laboratories : enhancing learning outcomes : final report. - Lowe, Dave; Murray, Steve; Li, Dikai; Lindsay, Euan (Australian Learning and Teaching Council (ALTC), 2008)
Remote laboratories provide access to the equipment within a physical laboratory through a Web interface, allowing students to utilise the equipment to undertake experiments without being physically present in the laboratory. The remote access can involve a range of interfaces from very simple text data through to complex controls, live video and audio feeds, and support for student collaboration. This project establishes a solid pedagogic framework for guiding the use of remote laboratories. This will help ensure that remote laboratories are able to effectively support improved student learning, whilst retaining the logistical and resourcing benefits which accrue from their use.